P03.03 Organization, function and gene expression of tertiary lymphoid structures in PDAC resembles lymphoid follicles in secondary lymphoid organs. (1st October 2020) - Thelen, M; García-Márquez, MA; Nestler, T; Wagener-Ryczek, S; Lehmann, J; Staib, E; Popp, F; Gebauer, F; Lohneis, P; Odenthal, M; Merkelbach-Bruse, S; Bruns, C; et al.
Abstract : Background: Secondary lymphoid organs (SLO) are involved in induction and enhancement of anti-tumor immune responses on different tumor entities. Recent evidence suggests that anti-tumor immune responses may also be induced or enhanced in the tumor microenvironment in so called tertiary lymphoid structures (TLS). It is assumed that TLS represent a hotspot for T cell priming, B cell activation, and differentiation, leading to cellular and humoral anti-tumor immune response. Methods: FFPE-slides of 120 primary pancreatic ductal adenocarcinoma (PDAC) patients were immunohistochemically (IHC) stained for CD20, CD3, CD8 and HLA-ABC to analyze spatial distribution of tumor-infiltrating lymphocytes. 5-color immunofluorescence staining was performed to further investigate structural components of TLS in comparison to lymphoid follicles in SLOs. Microscope-based laser microdissection and Nanostring-base RNA expression analysis were used to compare gene expression in PDAC, TLS, SLOs and normal pancreatic tissue. Results: TLS were frequently detected in PDAC and were mainly localized along the invasive tumor margin. In less than 10% of the cases TLS were infiltrating the tumors. Interestingly, 20% of the patients had no TLS. Results of TLS will be correlated with clinical parameters, Immunoscore and immune escape mechanisms. 5-color Immunofluorescence staining revealed similar organization and function of TLS and SLO. Finally, gene expression analyzed by Nanostring revealed largely overlapping expression patterns in TLS and SLO. Conclusions: The results clearly demonstrate close similarities between SLO and TLS in terms of composition, distribution and gene expression Patterns. Disclosure Information: M. Thelen: None. M.A. García-Márquez: None. T. Nestler: None. S. Wagener-Ryczek: None. J. Lehmann: None. E. Staib: None. F. Popp: None. F. Gebauer: None. P. Lohneis: None. M. Odenthal: None. S. Merkelbach-Bruse: None. C. Bruns: None. K. Wennhold: None. M. von Bergwelt-Baildon: None. H.A. Schlößer: None.